1995
DOI: 10.1002/ppul.1950190612
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship between postocclusional oscillatory pressure transients and standard lung function in healthy and asthmatic children

Abstract: We studied the correlation between characteristics of the postocclusional oscillatory airway opening pressure transients after flow interruption and body height, the degree of pulmonary hyperinflation [measured by thoracic gas volume (TGV)], and the degree of airway obstruction [measured by airway resistance (Raw)] and maximal expiratory flow at 50% vital capacity (MEF50) in 10 healthy and 50 asthmatic children age 7-16 years. Focusing on the damped oscillatory change in pressure, the first derivative of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…In our previous work, we also found only a single antiresonance in the power spectrum of Pao(t ') [13,14]. We have speculated that this single antiresonance is caused by an acoustic phenomenon of the air in the airways.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…In our previous work, we also found only a single antiresonance in the power spectrum of Pao(t ') [13,14]. We have speculated that this single antiresonance is caused by an acoustic phenomenon of the air in the airways.…”
mentioning
confidence: 73%
“…We have speculated that this single antiresonance is caused by an acoustic phenomenon of the air in the airways. We demonstrated that the damping properties of these oscillations are sensitive to airway mechanics, and change during bronchial challenge test in children [13,14]. This is especially interesting, since these oscillatory pressure transients are highly damped and independent of complete equilibration between alveolar and airway opening pressure.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Medidas como complacência (C), resistência (R), monitorização contínua de gases arteriais e volume de oclusão das vias aéreas podem ser avaliadas e complementam o estudo da função pulmonar 2,8,[17][18][19][20][21][22][23] .…”
Section: Introductionunclassified